Identification of business ideas for creation of company in the displaced population of Florencia, Colombia (2016)
The aim of this paper is to identify business ideas in the displaced population in the city of Florencia, Colombia, as a vital input to the generation of viable enterprises. It was worked with 56 people of the residential La Bocana of Florencia – Caquetá, which 32% were men and 68% women. It was applied a survey that allowed to recognize the business ideas, as well as the actions they have taken to implement them. The results show that 75% of respondents have thought in creating a business. Most relevant business ideas are: dressmaking, grocery store, and handicrafts, which are in concord with the families conformations, because these are mono-parenting, headed by women. Similarly, business ideas are related with the trade dynamics of municipality, where trade is a fundamental part of its economy, followed by the small industry of guadua-work, wood, and indigenous handicrafts. In this regard, it is appropriate to use the business plan as a tool that allows the generation of viable enterprises, as an alternative for improving the economic situation in a population as vulnerable as the displaced people.